The breeding of White Fulani cattle at Shika, Nigeria - Foster, W.H. (1960)
Reviews breeding work carried out over the period 1929-58 in the herd of White Fulani cattle kept at Shika government research station in Northern Nigeria. Topical discussions on the effects of various environmental factors on milk production in the herd; influence of breeding practices on genetic gain of animals, taking into account the environmental variation; and variation in birth weight and weight of heifer at two years included. Description of the purpose of the Shika herds, which has been recently reassessed, and the genetical methods by which its present aims are being pursued are outlined.